Peroxisomes from the heavy mitochondrial fraction: isolation by zonal free flow electrophoresis and quantitative mass spectrometrical characterization - Islinger, Markus; Li, Ka Wan; Loos, Maarten; Liebler, Sven Stefan; Angermüller, Sabine; Eckerskorn, Christoph; Weber, Gerhard; Abdolzade, Afsaneh; Völkl, Alfred (Journal of proteome research, 2010)
Peroxisomes are a heterogeneous group of organelles fulfilling reactions in a variety of metabolic pathways. To investigate if functionally different subpopulations can be found within a single tissue, peroxisomes from the heavy mitochondrial fraction (HM-Po) of the rat liver were isolated and compared to “classic” peroxisomes from the light mitochondrial fraction (LM-Po) using iTRAQ tandem mass spectrometry. Peroxisomes represent only a minor although significant proportion of the heavy mitochondrial fraction (2700gmax) precluding a straightforward isolation by standard protocols. Thus, a new fractionation scheme suitable for a subsequent mass spectrometrical analysis was developed using a combination of centrifugation techniques and zonal free flow electrophoresis. On the basis of the iTRAQ-measurement, a variation of the peroxisomal protein pattern between both fractions could be determined and further confirmed by immunoblotting and enzyme activity assays for selected proteins: whereas peroxisomes from the light mitochondrial fraction contain high amounts of β-oxidation enzymes, peroxisomes from the heavy mitochondrial fraction were dominated by enzymes fulfilling other functions. Among other findings, HM-Po was characterized by a high abundance of D-amino acid oxidase. This observation can be mirrored at the ultrastructural level, where tissue sections of liver peroxisomes show a heterogeneous staining for the enzymes activity, when visualized by the cerium technique.